Endotoxin downregulates rat hepatic ntcp gene expression via decreased activity of critical transcription factors. - Michael Trauner; Marco Arrese; Hyunjung Lee; James L. Boyer; Saul J. Karpen (1998)
Sodium-dependent uptake of bile acids across the hepatic basolateral membrane is rapidly and profoundly diminished during sepsis, thus contributing to the pathogenesis of sepsis-associated cholestasis. This effect is mediated by endotoxin or effector cytokines, which reduce expression of several hepatobiliary transporters, including the sodium-dependent bile acid transporter gene, ntcp. We test here the hypothesis that endotoxin treatment leads to impaired binding activity of ntcp promoter trans-acting factors, resulting in reduction of ntcp mRNA expression. After endotoxin administration, ntcp mRNA levels reached their nadir by 16 h, and nuclear run-on assays demonstrated a marked reduction in ntcp gene transcription. At 16 h after treatment, nuclear binding activities of two key factors that transactivate the ntcp promoter, hepatocyte nuclear factor (HNF) 1 and Footprint B binding protein (FpB BP), decreased to 44 and 47% of pretreatment levels, respectively, while levels of the other known ntcp promoter transactivator, signal transducer and activator of transcription 5, were unaffected. In contrast, the universal inflammatory response factors nuclear factor kappaB and activating protein 1 were both upregulated significantly. Examination of nuclear extracts obtained at sequential time points revealed that the maximal decrease in nuclear activities of both HNF1 and FpB BP preceded the nadir of ntcp mRNA expression by 6-10 h. Furthermore, these two nuclear factors returned towards normal levels before the recovery of ntcp mRNA levels observed by 48 h. Since HNF1alpha mRNA levels were unchanged at all time points, HNF1 is likely to be regulated posttranscriptionally by endotoxin. We conclude that the downregulation of ntcp gene expression by endotoxin is mediated at the level of transcription through tandem reductions in the nuclear binding activity of two critical transcription factors. These findings provide new insight into the coordinated downregulation of hepatobiliary transporters during sepsis.